Solar hot plates / Omar Ahmad - Ahmad, Omar (1985)
The solar energy has become recognised as one of the most important source of energy. Since increasing the price of petrol, gas, diesel and etc. rapid research has been done by most of the developed state in the world to used solar energy. Method of collecting solar energy has been improved as to transfer all the energy gain to useful work. Several type of collector had been design. For the purpose of this project a concentrated solar collector is discuss (Parabolic shape collector).